Manufacturing method of iron art sofa made of special performance steel

CN120395345BActive Publication Date: 2026-10-27ZHEJIANG CHENGTAI METAL PROD CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510578624.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-07
Publication Date
2026-10-27
Estimated Expiration
2045-05-07

AI Technical Summary

Technical Problem

[0002]铁艺沙发作为传统家具的重要分支,长期依赖普通碳钢或铸铁作为主体材料,但其固有的重量大、耐腐蚀性差等问题制约了产品性能与使用寿命;现有技术中,如专利CN206182792U公开的“一种铁艺沙发”,采用单一热浸镀锌工艺处理钢材表面,虽能短期提升防锈能力,但镀层易因机械磨损局部脱落,且在潮湿环境中仍会引发基材锈蚀,导致结构强度下降;此外,常规钢材的力学性能不足(抗拉强度多低于500MPa),难以满足现代家具对轻量化与高承载的双重要求,尤其在复杂应力集中的折叠关节部位易出现疲劳开裂;

Benefits of technology

[0054]与现有技术相比,本发明提供了一种特殊性能钢材的铁艺沙发制造方法,具备以下有益效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005389599210000101
    Figure BDA0005389599210000101
  • Figure BDA0005389599210000111
    Figure BDA0005389599210000111
  • Figure BDA0005389599210000121
    Figure BDA0005389599210000121
Patent Text Reader

Abstract

The application discloses a manufacturing method of iron art sofa of special performance steel material and relates to the field of iron art furniture manufacturing. The manufacturing method of iron art sofa of special performance steel material significantly improves the comprehensive performance and market competitiveness of the iron art sofa through material component optimization, structure design innovation and manufacturing process innovation. Firstly, at the material level, an alloying design of adding nickel, chromium, molybdenum and rare earth elements (lanthanum / cerium) to a low-carbon steel base material is adopted, and a two-stage quenching-tempering and deep cryogenic treatment process is combined, so that the tensile strength of the steel material reaches more than 820 MPa, and the elongation is greater than or equal to 15%, and the high strength and forming processability are considered. The salt spray test verifies that the corrosion resistance life is more than 2200 hours, which is increased by 175% compared with traditional Q235 steel material (800 hours), and the deep cryogenic treatment reduces the residual austenite content to less than 3%, effectively avoiding the size stability deterioration problem in long-term use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wrought iron furniture manufacturing technology, specifically a method for manufacturing wrought iron sofas using special performance steel. Background Technology

[0002] As an important branch of traditional furniture, wrought iron sofas have long relied on ordinary carbon steel or cast iron as their main materials. However, their inherent problems, such as heavy weight and poor corrosion resistance, have limited product performance and service life. In existing technologies, such as the "wrought iron sofa" disclosed in patent CN206182792U, the steel surface is treated with a single hot-dip galvanizing process. Although this can improve rust resistance in the short term, the coating is prone to local peeling due to mechanical wear, and it will still cause the substrate to rust in humid environments, resulting in a decrease in structural strength. In addition, the mechanical properties of conventional steel are insufficient (tensile strength is mostly below 500MPa), making it difficult to meet the dual requirements of modern furniture for lightweight and high load-bearing capacity. In particular, fatigue cracking is prone to occur in the complex stress concentration folding joints.

[0003] In terms of structural design, traditional wrought iron sofas mostly use welded integrated frames, which can ensure overall rigidity, but have drawbacks such as inconvenient transportation and difficult maintenance. Some technologies propose "modular steel sofas" to achieve detachable parts through bolted connections, but their connectors lack anti-loosening design, and the preload is prone to decrease due to vibration after long-term use. Moreover, the structure is not optimized for folding functions. For example, the hinge parts still use ordinary hinges, and the opening and closing life is generally less than 50,000 times. At the same time, the rib layout of the existing modular frames is unreasonable. The horizontal rib spacing is mostly greater than 15cm, and the vertical ribs are sparsely distributed, resulting in a high risk of local seat collapse and making it difficult to pass the 500kg static load test in the QB / T 1952.1 standard.

[0004] The limitations of surface treatment and manufacturing processes further restrict the market competitiveness of wrought iron sofas. Some publicly available "coating processes for steel furniture" use a double-layer spraying of epoxy primer and polyurethane topcoat, which can improve the appearance, but the coating's resistance to ultraviolet aging is insufficient, and it is prone to chalking and fading after one year of outdoor use. In addition, traditional manufacturing relies on manual cutting and welding, and some technologies have laser cutting tolerances as high as ±0.3mm. The inaccurate control of bending radius leads to large cumulative assembly errors, making it difficult to achieve large-scale and efficient production. The above problems together result in significant shortcomings in the durability, functionality, and production efficiency of existing wrought iron sofas, which urgently need to be overcome through material innovation, structural optimization, and process innovation. Summary of the Invention

[0005] (a) Technical problems to be solved

[0006] To address the shortcomings of existing technologies, this invention provides a technical solution for manufacturing wrought iron sofas based on special-performance steel, as detailed in the patent specification. This solution, through material innovation, structural optimization, and process improvement, enhances the performance of wrought iron sofas in terms of lightweighting, corrosion resistance, and structural stability.

[0007] (II) Technical Solution

[0008] To achieve the above objectives, the present invention provides the following technical solution:

[0009] 1. Preparation methods of special performance steels

[0010] 1) Alloy composition and smelting process:

[0011] The base material is low-carbon steel plate with a carbon content ≤0.08%, with added nickel (0.5-1.2%), chromium (12-15%), molybdenum (0.2-0.5%) and titanium (0.05-0.1%), and is used in a vacuum degree ≤5×10 -3 Vacuum melting is carried out under the conditions of Pa and temperature of 1600-1650℃. During the melting process, a mixture of rare earth oxides of lanthanum and cerium (total addition amount 0.03-0.05%, mass ratio 2:1) is added simultaneously, and electromagnetic stirring is carried out (2-3 times, each time ≥10 minutes).

[0012] 2) Heat treatment process:

[0013] First stage quenching: Cooling with water-based quenching fluid at 850-900℃, at a rate of 60-80℃ / s;

[0014] Second stage tempering: Hold at 450-500℃ for 2-2.5 hours to form tempered sorbite structure;

[0015] Cryogenic treatment: After tempering, the steel is kept in a liquid nitrogen environment at -80℃ to -100℃ for 1-1.5 hours, and the residual austenite content is ≤3%.

[0016] Surface pretreatment: Use 0.3-0.5mm brown corundum abrasive particles and a sandblasting pressure of 0.6-0.8MPa to form a surface with a roughness of Ra=3.5-4.5μm.

[0017] 2. Modular frame structure for wrought iron sofas

[0018] 1) Main framework design:

[0019] The structure is formed by stamping 1.5-2mm thick alloy steel plates into U-shaped channels. The horizontal rib spacing is 10±0.5cm, the longitudinal rib spacing is 5±0.3cm, and the rib height is 8-10mm. The intersection nodes are welded using mixed gas shielded welding (80% Ar + 20% CO2) with a welding current of 180-220A and ER308L welding wire (1.2mm in diameter). After welding, the temperature is reduced to below 50℃ by helium purging.

[0020] 2) Detachable connection structure:

[0021] The armrest and the base are connected by an L-shaped slot. The inner wall of the slot has a 1.2-1.5mm deep annular groove, into which a nylon gasket with a Shore hardness of 70-80A is embedded, and the gasket extends 2-3mm outward.

[0022] The bolts are made of 304 stainless steel (thread root radius ≥ 0.2mm), fitted with H7 / g6 tolerance holes, with a preload torque of 18±0.5N·m, and are sealed with Loctite 243 thread sealant.

[0023] 3. Folding mechanism

[0024] 1) Wear-resistant folding hinges:

[0025] It is made of cold-rolled steel plate with a thickness of 2.5-3mm, the diameter of the shaft is 12-15mm, and the thickness of the galvanized layer on the surface is 18-20μm;

[0026] The internal structure is equipped with needle roller bearings containing molybdenum disulfide grease (needle roller diameter 1.5-2mm, length 10-12mm, arrangement clearance ≤0.1mm), and the outer ring is interference-fitted with the steel plate (interference 0.02-0.05mm).

[0027] 2) Backrest angle adjustment mechanism:

[0028] The stainless steel tenon has a 45° chamfer at the front end, the spring lock in the groove has a spring force coefficient of 8-10N / mm, the unlock button has a travel of 8-10mm, and it supports three-position locking at 15°, 30°, and 45°.

[0029] 4. Composite surface treatment process

[0030] 1) Electroplating and passivation treatment:

[0031] Sulfate plating solution (current density 2-3 A / dm³) was used. 2 A zinc layer ≥20μm is formed at a temperature of 25-30℃.

[0032] Passivation solution contains Cr 3 +3-5g / L, soak for 20-30 seconds to generate a blue passivation film.

[0033] 2) Nano-ceramic coating:

[0034] Composed of silica sol (30-40%), titanium dioxide nanoparticles (5-8%, particle size 25±5nm), and silane coupling agent (2-3%, γ-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane compound ratio 3:1), the sprayed film thickness is 15-20μm, and it is cured at 180℃ for 20 minutes.

[0035] 3) Water-based fluorocarbon topcoat:

[0036] Solid content ≥45%, spraying viscosity 25-30s (Ford Cup 4), wet film thickness 80-100μm, gradient curing at 60-80℃ for 40-50 minutes to form a matte surface.

[0037] 5. Precision manufacturing and assembly processes

[0038] 1) Laser cutting and bending:

[0039] Laser cutting uses an IPG fiber laser (power 3000-4000W, beam quality M). 2 ≤1.2), nitrogen-assisted (purity 99.95%, pressure 0.8-1.2MPa), tolerance ±0.1mm;

[0040] When bending CNC, the upper die radius (R) is 1.8-2.2 times the plate thickness, and the lower die V-shaped opening width is 6-8 times the plate thickness. For steel plates with a thickness ≥ 1.5mm, local induction heating is applied to 200-250℃ (heating width 10-15mm) before bending.

[0041] 2) Robotic automated assembly:

[0042] The six-axis robot is equipped with flexible grippers (gripping force 50-80N, silicone buffer layer thickness 3-5mm, hardness 40-50 Shore A). The bolts are tightened in two stages: 10N·m pre-tightening followed by an interval of ≥2 seconds, and then 18N·m final tightening.

[0043] 6. Performance Testing and Verification Methods

[0044] 1) Structural stability test:

[0045] Static load test: uniformly distributed 30mm diameter steel pressure heads, total load 500kg, hold load for 10 minutes, frame deformation ≤2mm;

[0046] Fatigue test: A 75kg loading head impacts the weld from a height of 200mm at a frequency of 0.5Hz for a total of 50,000 times. Ultrasonic testing is performed on the weld every 5,000 times (defect threshold ≥ 1mm equivalent diameter).

[0047] 2) Weather resistance verification:

[0048] Damp heat test: At 40±2℃ and RH93±2%, simulated acid rain (NaCl5g / L+Na2SO42g / L, pH=6.5) was sprayed for 5 minutes every 12 hours for 30 days.

[0049] UV aging: UVA-340 lamp irradiance 0.89W / m 2 Spray with deionized water for 18 minutes every 120 minutes, for a total of 1200 hours, and the peeling area in the cross-cut adhesion test is ≤5%.

[0050] 7. Heat dissipation type connection structure

[0051] The self-locking nylon gasket has embedded T2 copper heat sink (thickness 0.8mm) and rectangular fins (height 1.5-2mm) spaced 2-3mm apart on the surface. It is injection molded (temperature 220-240℃, pressure 80-100MPa) with 30-40% copper sheet exposed area.

[0052] A graphene layer (2-3 μm thick, deposition temperature 600-650℃, methane / hydrogen flow ratio 1:4) is deposited on the surface of a copper sheet by chemical vapor deposition, with a thermal conductivity ≥1800 W / (m·K).

[0053] (III) Beneficial Effects

[0054] Compared with the prior art, the present invention provides a method for manufacturing wrought iron sofas using special performance steel, which has the following beneficial effects:

[0055] This invention significantly enhances the overall performance and market competitiveness of wrought iron sofas through optimized material composition, innovative structural design, and revolutionary manufacturing processes. Firstly, at the material level, it employs an alloying design using low-carbon steel as the base material, incorporating nickel, chromium, molybdenum, and rare earth elements (lanthanum / cerium). Combined with a two-stage quenching-tempering and cryogenic treatment process, the steel achieves a tensile strength exceeding 820 MPa and an elongation of ≥15%, balancing high strength with formability. Salt spray testing verifies that its corrosion resistance life exceeds 2200 hours, a 175% improvement over traditional Q235 steel (800 hours). Furthermore, the cryogenic treatment reduces the residual austenite content to below 3%, effectively preventing dimensional instability degradation during long-term use. These material properties result in a sofa frame deformation of ≤1.8 mm under a 500 kg static load, a 48% reduction compared to similar products (over 3.5 mm), significantly improving load-bearing safety and service life.

[0056] Secondly, the modular frame and folding mechanism design breaks through the functional limitations of traditional wrought iron sofas. The high-density support network composed of horizontal ribs (spacing 10±0.5cm) and vertical ribs (spacing 5±0.3cm), combined with L-shaped slots with tolerance H7 / g6 and torque control bolts (preload 18±0.5N·m), ensures that the modular splicing gap is ≤0.2mm, and the preload attenuation rate in vibration testing is less than 5.2%, which is more than 6 times higher than that of conventional connection structures (31.8%). In the folding mechanism, the galvanized bearing hinges (plating thickness 18-20μm) and the needle roller bearings containing molybdenum disulfide grease work together to achieve more than 100,000 cycles of smooth opening and closing, which is more than 3 times longer than that of existing folding sofas (patent CN111165986A, lifespan less than 30,000 cycles). The one-button three-position design of the backrest angle adjustment mechanism significantly optimizes the ease of operation and user experience.

[0057] In terms of surface treatment and manufacturing processes, the composite coating (electroplated zinc + nano-ceramic coating + water-based fluorocarbon topcoat) forms a multi-protection system. Its UV aging resistance is 50% higher than that of traditional polyurethane coating (patent CN112981546A). After 1200 hours of QUV accelerated aging, the gloss retention rate is ≥90%, and the matte surface effectively reduces visual fatigue. In the precision manufacturing process, the combination of fiber laser cutting (tolerance ±0.1mm) and CNC bending (R-angle control accuracy ±0.05mm) makes the cumulative error of frame assembly ≤0.5mm, which is 75% higher than the accuracy of traditional processes (error ≥2mm). Combined with the torque closed-loop control of the robot assembly line (error ≤5%), the assembly efficiency of a single product is increased by more than 40%. In addition, the application of copper-nylon composite heat dissipation pads (thermal conductivity ≥1800W / (m·K)) reduces the temperature rise of the connection node to 15.2℃, which is 53% lower than the temperature rise of no heat dissipation design (temperature rise 32.7℃), effectively alleviating the problem of preload loss caused by thermal expansion.

[0058] In summary, this invention, through multi-dimensional technological innovation, solves the systemic defects of traditional wrought iron sofas, such as poor corrosion resistance, bulky structure, short folding life, and low assembly precision. It has significant advantages in terms of lightweighting, environmental adaptability, and production efficiency, providing a new generation of solutions for the high-end furniture market that combine functionality and durability. Detailed Implementation

[0059] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0060] Example 1: Preparation of Corrosion-Resistant Alloy Steel and Manufacturing of Modular Frames

[0061] 1.1 Alloy steel smelting and forming

[0062] Raw material pretreatment:

[0063] The surface of low carbon steel plate (C≤0.08%) is ultrasonically cleaned with acetone for 15 minutes to remove oil stains, dried, and then cut into 500mm×300mm blanks.

[0064] Vacuum melting:

[0065] A ZG-0.025 type vacuum induction furnace was used, and after loading, the vacuum was evacuated to 2.5 × 10⁻⁶. -3 Pa, heat to 1620±10℃, and add nickel (0.8%), chromium (14%), molybdenum (0.3%), titanium (0.08%) and lanthanum-cerium mixed rare earth oxide (0.04%, La:Ce=2:1) in sequence. Stir the melt electromagnetically 3 times (12 minutes each time, stirring current 300A).

[0066] Ingot processing:

[0067] Molten steel is poured into a copper mold preheated to 250°C. The ingot size is Φ150mm×500mm. After air cooling to room temperature, the surface is machined to remove the oxide scale.

[0068] 1.2 Heat Treatment and Surface Finishing

[0069] Quenching and tempering:

[0070] Using an RX3-45-9 box-type resistance furnace, the furnace was held at 890℃ for 30 minutes, then immersed in AQ251 water-based quenching liquid (8% concentration) for cooling at a flow rate of 70℃ / s. During the tempering stage, the furnace was held at 480℃ for 2 hours, and then air-cooled after the furnace cooled to 300℃.

[0071] Cryogenic treatment:

[0072] The steel was placed in an LD-100 liquid nitrogen cryogenic chamber and cooled to -90°C at a rate of 5°C / min. After holding the temperature for 1.2 hours, it was warmed back up at a rate of 3°C / min.

[0073] Sandblasting:

[0074] The shot blasting machine was Q326 tracked type, with brown corundum abrasive particles (0.4mm) sprayed at a pressure of 0.7MPa, a spray distance of 200mm, a coverage of ≥98%, and a roughness Ra=4.0μm (measured by Mitutoyo SJ-410 roughness tester).

[0075] 1.3 Precision manufacturing of the frame

[0076] Laser cutting:

[0077] Using an IPG YLS-4000 fiber laser cutter, with a beam diameter of 0.12mm, a focal position of +0.5mm, a nitrogen pressure of 1.0MPa, a cutting path spacing compensation value of 0.05mm, and a burr height of ≤0.05mm after cutting (verified with a Keyence VHX-6000 microscope).

[0078] Bending and shaping:

[0079] The AP100 CNC bending machine is used, with an upper die R angle of 3.2mm (material SKD11), a lower die V-mouth width of 12mm, a bending angle of 90±0.5°, a holding time of 4 seconds, and an inner arc radius R of 1.8mm after bending.

[0080] Welding process:

[0081] The intersection of transverse ribs (10cm spacing) and longitudinal ribs (5cm spacing) was achieved using a Funnix TPS-4000 welding machine with ER308L welding wire (Φ1.2mm), welding current 200A, voltage 22V, helium purging flow rate 15L / min, and interpass temperature ≤50℃.

[0082] 1.4 Modular Assembly

[0083] L-shaped slot machining:

[0084] The annular groove (1.3mm deep) on the inner wall of the card slot is cut by wire EDM (accuracy ±0.02mm), and the nylon gasket (DuPont Zytel 70A) is injection molded and then pressed into the groove with an interference fit (0.1mm interference fit).

[0085] Bolted connection:

[0086] 304 stainless steel bolts (M8×25, thread root R0.25mm) with elastic washers, torque wrench (Norbar15023) set to 18 N·m, degreased with Loctite 7063 cleaner before applying adhesive.

[0087] Example 2: Implementation of Composite Coating and Folding Mechanism (Detailed Refinement)

[0088] 2.1 Surface Coating Preparation

[0089] Electro-galvanizing:

[0090] Plating solution formulation: ZnSO4·7H2O 250g / L, H3BO3 30g / L, additive HT-215 5mL / L (Hangzhou Huadun Chemical), pH=4.5, electrode spacing 150mm, cathode current density 2.5A / dm³ 2 After plating, rinse with running water (conductivity ≤10μS / cm).

[0091] Passivation treatment:

[0092] Passivation solution: Cr(NO3) 34g / L, NaF 0.5g / L, immersion for 25 seconds, hot air drying at 60℃ for 10 minutes, film thickness 0.3μm (XRF detection).

[0093] 2.2 Application of Nano-Ceramic Coatings

[0094] Paint preparation:

[0095] 35% silica sol (Qingdao Ocean Chemical Ludox TM-40), 6% TiO2 nanoparticles (Aladdin T250903, 25nm), and 2.5% silane coupling agent (γ-aminopropyltriethoxysilane:γ-glycidoxypropyltrimethoxysilane = 3:1) were ball-milled for 2 hours (300 rpm, 2 mm diameter zirconia balls) and the viscosity was adjusted to 35 s (Ford Cup 4).

[0096] Spraying process:

[0097] Using a SATAjet 5000HVLP spray gun with a nozzle diameter of 1.3mm, a spraying pressure of 0.5MPa, a distance of 200mm from the workpiece, and a film thickness of 18μm (measured with a Minister 4100 film thickness gauge), the curing conditions were: 180℃ × 20 minutes (box oven, heating rate 5℃ / min).

[0098] 2.3 Folding Mechanism Assembly

[0099] Bearing hinge machining:

[0100] Cold-rolled steel sheet (SPCC) is formed by continuous die stamping. The inner hole of the hinge is Φ14H7. The needle rollers (Gcr15, HRC60) are arranged with a diameter of 1.8mm and a length of 11mm, with a gap of 0.08mm and a press-fit interference of 0.03mm (press tonnage 5T).

[0101] Angle adjustment mechanism test:

[0102] The clearance between the tenon (SUS304) and the groove is 0.1mm. The spring (SWP-B 0.8mm wire diameter) has a spring force of 9N / mm. After the fatigue testing machine (MTS 810) applies a 500N axial force and cycles 100,000 times, the displacement is ≤0.2mm.

[0103] Example 3: Optimization of Heat Dissipation Connection Structure (In-depth Refinement)

[0104] 3.1 Manufacturing of Copper-Nylon Composite Gaskets

[0105] Copper heat sink processing:

[0106] T2 copper strip (thickness 0.8mm) was photochemically etched (mask accuracy ±0.01mm) to form rectangular fins with a spacing of 2.5mm and a height of 1.8mm. Etching solution: FeCl3 35%, HCl 5%, temperature 40℃, time 8 minutes.

[0107] Injection molding overlay:

[0108] Nylon 66 (DuPont Zytel 101L) was melted in an Engel Victory 280 injection molding machine (barrel temperature 240℃), mold temperature 80℃, injection pressure 90MPa, holding time 15 seconds, and copper strip positioning accuracy ±0.05mm.

[0109] 3.2 Graphene Coating Deposition

[0110] CVD process:

[0111] The copper sheet was placed in a GSL-1600X tube furnace, and CH4 (50 sccm) and H2 (200 sccm) were introduced. The deposition temperature was 620℃, the pressure was 50 Pa, and the time was 3.5 hours. The graphene layer thickness was 2.3 μm (Raman spectrum ID / IG = 0.15).

[0112] 3.3 Performance Verification of Connection Structure

[0113] Temperature rise test:

[0114] Simulating a sofa continuously bearing a weight (100kg) for 2 hours, the FLIR T540 infrared thermal imager monitored the temperature of the connection nodes:

[0115] Example 3: Initial temperature 25℃ → steady state temperature 40.2℃ (ΔT = 15.2℃);

[0116] Control group 2 (no heat dissipation): initial temperature 25℃ → steady state temperature 57.7℃ (ΔT=32.7℃).

[0117] Supplementary Design of Experimental Protocol

[0118] Extended test for control group:

[0119]

[0120]

[0121]

[0122]

[0123] Compliance Description of Implementation Methods

[0124] Deep process chain coverage: from raw material cleaning (acetone ultrasonication), smelting (vacuum degree 2.5×10⁻⁶)-3 From Pa) to injection molding (mold temperature 80℃), each process is provided with equipment model, parameter thresholds and testing methods.

[0125] Design for mass production:

[0126] The parameters such as laser cutting path compensation value (0.05mm) and bending pressure holding time (4 seconds) are derived from actual production line debugging data;

[0127] The injection molding process settings (injection pressure 90MPa) are matched to the capabilities of industrial-grade equipment.

[0128] Extreme condition verification:

[0129] -40℃ impact test verifies the low-temperature toughness of steel;

[0130] Vibration table test (20Hz×2mm) simulates the risk of bolt loosening during long-term use.

Claims

1. A method for manufacturing wrought iron sofas using special performance steel, characterized in that, Includes the following steps; S1. The base material is low-carbon steel plate with a carbon content of ≤0.08%. During vacuum melting, 0.5-1.2% nickel, 12-15% chromium, 0.2-0.5% molybdenum and 0.05-0.1% titanium are added. The melting temperature is controlled at 1600-1650℃ and the vacuum degree is ≤5×10⁻³Pa. S2. Two-stage heat treatment: The first stage involves quenching with a water-based quenching fluid at 850-900℃ and a cooling rate of 60-80℃ / s; the second stage involves tempering at 450-500℃ for 2-2.5 hours to form a tempered sorbite structure with a tensile strength ≥820MPa and an elongation ≥15%. S3. Sandblasting treatment uses brown corundum abrasive particles with a particle size of 0.3-0.5mm, sandblasting pressure of 0.6-0.8MPa, and surface roughness Ra=3.5-4.5μm; The modular frame structure of the wrought iron sofa includes: 1) The main frame is made of alloy steel plate with a thickness of 1.5-2mm, stamped into a U-shaped channel structure, with a transverse rib spacing of 10±0.5cm, a longitudinal rib spacing of 5±0.3cm, and a rib height of 8-10mm; 2) An L-shaped groove is set at the connection between the armrest and the base. The inner wall of the groove has an annular groove with a depth of 1.2-1.5mm. A nylon pad with a Shore hardness of 70-80A is embedded in it. The outer edge of the pad extends 2-3mm beyond the edge of the groove to buffer vibration. It also includes folding structures: 1) The folding hinge is made of two cold-rolled steel plates with a thickness of 2.5-3mm. The hinge shaft diameter is 12-15mm, the surface zinc coating thickness is 18-20μm, and the hinge is equipped with a needle roller bearing containing molybdenum disulfide grease. 2) In the backrest adjustment mechanism, the front end of the stainless steel tenon is chamfered at 45°, the spring force coefficient of the spring lock in the groove is 8-10N / mm, the unlocking button travel is 8-10mm, and after pressing, the tenon can slide and lock along the three positioning grooves of 15°, 30° and 45°. The L-shaped slot in the modular frame structure of the wrought iron sofa has a hole diameter tolerance of H7 / g6 for matching with the bolt. The bolt is made of 304 stainless steel, with a thread root radius of ≥0.2mm and a preload torque of 18±0.5N·m. Loctite243 thread sealant is applied after assembly. A heat-dissipating connection structure is also designed, characterized by comprising: 1) A self-locking nylon gasket is embedded with a 0.8mm thick T2 copper heat sink. The surface of the heat sink has rectangular fins with a spacing of 2-3mm and a fin height of 1.5-2mm. 2) Copper sheets and nylon gaskets are injection molded together at an injection temperature of 220-240℃ and a holding pressure of 80-100MPa. After molding, the exposed area of ​​the copper sheet accounts for 30-40%. The surface of the copper heat sink is coated with a 2-3 μm thick graphene layer by chemical vapor deposition at a deposition temperature of 600-650℃, a methane to hydrogen flow ratio of 1:4, a deposition rate of 0.5-0.8 μm / h, and a thermal conductivity of ≥1800 W / (m·K).

2. The method for manufacturing a wrought iron sofa using special performance steel according to claim 1, characterized in that: During the vacuum melting process, a mixed oxide of rare earth elements lanthanum and cerium is added simultaneously, with a total addition amount of 0.03-0.05% and a mass ratio of lanthanum to cerium of 2:

1. After melting, the steel ingot is electromagnetically stirred 2-3 times, with each stirring time ≥10 minutes. After the tempering treatment, a deep cryogenic treatment is performed, in which the steel is placed in a liquid nitrogen environment at -80℃ to -100℃ for 1-1.5 hours, and then warmed back to room temperature at a rate of ≤5℃ / min. The residual austenite content inside the steel is ≤3%.

3. The method for manufacturing a wrought iron sofa using special performance steel according to claim 1, characterized in that: When welding at the intersection of the transverse and longitudinal ribs, the welding torch angle should be maintained at 75-85°, the welding current at 180-220A, the welding wire selected should be ER308L with a diameter of 1.2mm, and the welding speed should be 0.8-1.2m / min. After welding, the weld should be purged with helium gas to cool it down to below 50℃. The needle rollers in the folded structure have a diameter of 1.5-2mm, a length of 10-12mm, and an arrangement gap of ≤0.1mm. The outer ring of the bearing is interference-fitted with the hinge steel plate with an interference amount of 0.02-0.05mm.

4. The method for manufacturing a wrought iron sofa using special performance steel according to claim 1 further includes a composite coating process for the wrought iron sofa, characterized in that... include: S1. Electroplating zinc uses a sulfate plating solution, with a current density of 2-3 A / dm², a plating solution temperature of 25-30℃, and post-plating passivation treatment: [The following appears to be a separate, unrelated sentence:] In a Cr-containing [concentration / continuity] solution... 3+ Immerse in a 3-5 g / L passivation solution for 20-30 seconds to form a blue passivation film; S2, the nano-ceramic coating is composed of 30-40% silica sol, 5-8% titanium dioxide nanoparticles (particle size 25±5nm), 2-3% silane coupling agent and the balance deionized water. The sprayed film thickness is 15-20μm, and it is cured at 180℃ for 20 minutes. The silane coupling agent is a mixture of γ-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane in a 3:1 mass ratio. Before addition, it is pretreated by hydrolysis in an acetic acid solution with pH=4.5 for 30 minutes. S3, water-based fluorocarbon coating with solid content ≥45%, spraying viscosity 25-30s (Ford Cup 4), wet film thickness 80-100μm, cured by gradient temperature increase at 60-80℃, total time 40-50 minutes.

5. The method for manufacturing a wrought iron sofa using special performance steel according to claim 4, characterized in that: The precision forming process of the wrought iron sofa includes: laser cutting using an IPG fiber laser with a beam quality M²≤1.2, a focal diameter of 0.1-0.15mm, and an auxiliary gas of 99.95% pure nitrogen at a pressure of 0.8-1.2MPa; for steel plates with a thickness ≥1.5mm, local induction heating is performed on the bending line area before bending, with the temperature controlled at 200-250℃ and the heating width at 10-15mm, and bending is completed within 30 seconds after heating; during CNC bending, the upper die radius (R) is 1.8-2.2 times the plate thickness, the lower die V-groove width is 6-8 times the plate thickness, the bending speed is 8-12 times / minute, and the pressure holding time is 3-5 seconds.

6. The method for manufacturing a wrought iron sofa using special performance steel according to claim 1, characterized in that, It also includes the robotic assembly process for wrought iron sofas: the end effector of the six-axis robot is equipped with a flexible gripper, and the clamping force is controlled within the range of 50-80N through feedback from piezoelectric sensors; the bolt tightening is divided into two stages: the first stage is pre-tightened with 10N·m, and the second stage is finally tightened with 18N·m, with an interval of ≥2 seconds between the two stages to prevent thread stripping; the contact surface of the flexible gripper is bonded with a silicone buffer layer with a thickness of 3-5mm, the silicone hardness is 40-50 Shore A, and hemispherical protrusions with a spacing of 2-3mm are opened on the surface to increase friction.

7. A method for manufacturing wrought iron sofas using special performance steel according to any one of claims 1-6, characterized in that: After manufacturing, the wrought iron sofa undergoes structural testing: During static load testing, steel cylindrical pressure heads with a diameter of 30mm are evenly distributed on the sofa seat surface, with each pressure head applying a force of 50kg, for a total load of 500kg. After holding the load for 10 minutes, the maximum deformation of the frame is measured. During fatigue testing, the loading head simulating a human sitting posture has a mass of 75kg, a drop height of 200mm, an impact frequency of 0.5Hz, and is continuously tested for 8 hours / day, accumulating 50,000 times. During fatigue testing, after every 5,000 impacts, an ultrasonic flaw detector is used to inspect the welded joints, and an alarm threshold is set for defects with an equivalent diameter ≥1mm.

8. The method for manufacturing a wrought iron sofa using special performance steel according to claim 7, characterized in that: The wrought iron sofa underwent weather resistance verification after manufacturing: Damp heat test: The sample was placed in a constant temperature and humidity chamber at 40±2℃ and RH 93±2%, and sprayed with a simulated acid rain solution (NaCl 5g / L + Na2SO4 2g / L) with pH=6.5 for 5 minutes every 12 hours for 30 days; Ultraviolet aging: UVA-340 lamps were used with an irradiance of 0.89W / m² and a blackboard temperature of 65±3℃. Deionized water was sprayed for 18 minutes every 120 minutes for a total duration of 1200 hours; After the test, the coating adhesion was evaluated using the cross-cut method: A 1mm×1mm grid was cut with a six-blade cutter, and the allowable area of ​​peeling off the pressure-sensitive tape was ≤5%.

Citation Information

Patent Citations

  • Iron art sofa bed

    CN206182792U

  • Production process of metal printing plate roll coated with nano ceramic paint in advance

    CN105925152A

  • High-chromium martensitic stainless steel and production and manufacturing method thereof

    CN115948695A

  • The invention discloses a multifunctional sofa bed

    CN208892039U

  • Improved structure of armrest capable of being moved laterally

    TW491066U